The Inclusion and Literation Finance on MSME performance through adoption of financial reporting standard - Praptitorini, Mirna Dyah; Astohar, Astohar (Indonesia Auditing Research Journal, 2024)
MSMEs must monitor their financial health by preparing financial reports according to established standards. This affects the overall performance of SMEs, which is also influenced by other developing factors such as financial inclusion and financial literacy. This research aims to investigate how the application of financial reporting standards can help regulate the relationship between financial literacy and financial inclusion on the performance MSMEs in Semarang City. A structured questionnaire was used to collect quantitative data from MSME actors in 16 sub-districts of the city of Semarang. Sampling in this study used the cluster sampling method. There are 145 data samples available. Data analysis uses multiple regression and the Sobel test to identify mediating variables. The research results show that SME performance is significantly and positively influenced by financial literacy, financial inclusion and the adoption of financial reporting standards. The adoption of financial reporting standards can improve the relationship between financial literacy and financial inclusion on MSME performance. The contribution of this research is to increase understanding of the importance of financial literacy. financial inclusion and adoption of reporting standards. Financing that meets standards affects the performance of small and medium enterprises (SMEs) in the long term